Functional characterization of vitamin B12 from an extremophile—Pseudomonas alcaliphila and assessment of its microbial chassis potential - Venkatesan, Sathya Narayanan; Sankaranarayanan, Mugesh; Loganathan, Karthik (Frontiers in Microbiology, 2025)
IntroductionVitamin B12 (B12) is an essential cofactor for key metabolic processes in most living organisms, yet only certain bacteria can synthesize it de novo. Common forms of B12 include adenosylcobalamin (AdoCbl), methylcobalamin (MeCbl) and cyanocobalamin (CNCbl). This study presents the B12 production capability of an extremophile—Ectopseudomonas alcaliphila MSJ19, and a multilevel evaluation of bioactivity of various B12 forms.MethodsB12 extracted from Ectopseudomonas alcaliphila MSJ19 was initially analyzed by bioassay and LC–MS to confirm the presence of natural B12 forms, followed by in vitro enzyme activity assays with glycerol dehydratase (GD) and diol dehydratase (DD). The functionality of various B12 forms on these enzymes was further evaluated using in-silico molecular docking studies. The bioactivity at the in vivo level was assessed by introducing a coenzyme B12-dependent 3-hydroxypropionic acid (3-HP) biosynthetic pathway in E. coli W and Ectopseudomonas alcaliphila MSJ19 for their ability to transform glycerol into 3-HP.ResultsBioassay and LC–MS analysis confirmed the presence of ~7 μg/g cdw B12 in the processed extract and specific precursor-product ion transitions, indicated the production of natural B12 forms. To functionally validate the bioactivity of the crude B12 extract, the coenzyme B12-dependent 3-HP biosynthesis pathway was employed in recombinant E. coli W. Supplementation with different B12 forms revealed a hierarchical GD and DD activity (AdoCbl > MeCbl > CNCbl) and a dose-dependent increase in 3-HP production, with an optimal threshold around 500 nM. The conformational specificity of AdoCbl and competitive inhibition of CNCbl and MeCbl were supported by molecular docking of all 3 B12 forms with GD and DD. Notably, crude B12 extract at 0.35 nM yielded 5.9 mM 3-HP titer, closely matching the 7.8 mM obtained with AdoCbl, confirming its bioactive equivalence. Furthermore, recombinant Ectopseudomonas alcaliphila MSJ19 (EaMr) harboring the 3-HP pathway produced up to 3.3 mM 3-HP without external B12 supplementation, highlighting innate capability of the host to produce and utilize bioactive B12in vivo.DiscussionCollectively—in vitro, in silico and in vivo approaches establish a functional framework for certifying B12 bioactivity and demonstrating EaM as a potent chassis for production of value-added chemicals.